Consultation about urinary and faecal incontinence in the year after childbirth: a cohort study. (9th July 2014) - Brown, S; Gartland, D; Perlen, S; McDonald, E; MacArthur, C
<x xml:space="preserve">Abstract</x> Objective To investigate the extent to which primary‐care practitioners routinely inquire about postpartum urinary and faecal incontinence, and assess the proportion of women who disclose symptoms. Design Prospective pregnancy cohort study of nulliparous women. Setting Melbourne, Australia. Sample A total of 1507 nulliparous women recruited in early pregnancy. Method Women were recruited from six public maternity hospitals, with follow up at 3, 6, 9 and 12 months postpartum. Main outcome measures Standardised measures of urinary and bowel symptoms, and measures of health service use. Results In the first 12 months postpartum, the period prevalence of urinary incontinence was 47%, and of faecal incontinence was 17%. In all, 86% of women visited a primary health‐care practitioner at least once to discuss their own health in the first year after childbirth. However, only around a quarter were asked about urinary incontinence, and fewer than one in five women were asked about faecal incontinence. Discussion of symptoms with health professionals was most likely to occur in the first 3 months postpartum, and happened only rarely during the remainder of the first postnatal year. Over 70% of women reporting severe urinary incontinence and/or faecal incontinence had not discussed symptoms with a health professional. Conclusion The findings provide robust evidence that many women experiencing postpartum urinary and faecal incontinence—including women with moderate and severe symptoms—do not receive adequate primary‐care follow up in the first 12 months postpartum. Systems of maternal health surveillance need to include routine inquiry about urinary and faecal incontinence to overcome women's reluctance to seek help.